Sistem Pendukung Keputusan Rekomendasi Objek Wisata Terbaik di Kota Sabang menggunakan Metode Fuzzy Tsukamoto Berbasis Web - Rahmatullah (Journal Innovations Computer Science, 2024)
This research examines the implementation of a decision support system for tourism destination selection using the web-based Fuzzy Tsukamoto method. With the growing tourism industry and tourists' need for accurate recommendations, a system capable of processing uncertain data and providing optimal results is required. The Fuzzy Tsukamoto method was chosen for its ability to handle linguistic and uncertain data through fuzzification, rule evaluation, and defuzzification processes. The web-based system developed enables easy and widespread user access. The research employs qualitative and quantitative approaches by analyzing important criteria in tourism destination selection such as accessibility, facilities, price, and attractions. The results demonstrate that the Fuzzy Tsukamoto implementation can provide tourism destination recommendations that match user preferences with good accuracy levels. The resulting web-based system proves to be user-friendly and can assist tourists in making appropriate decisions. This research contributes to information technology development in the tourism sector and can serve as a reference for developing similar systems in the future.